Cathelicidin‐related antimicrobial peptide mediates skeletal muscle degeneration caused by injury and Duchenne muscular dystrophy in mice. Issue 6 (4th September 2022) - Choi, Moon‐Chang; Jo, Jiwon; Lee, Myeongjin; Park, Jonggwan; Yao, Tso‐Pang; Park, Yoonkyung
Abstract: Background: Cathelicidin, an antimicrobial peptide, plays a key role in regulating bacterial killing and innate immunity; however, its role in skeletal muscle function is unknown. We investigated the potential role of cathelicidin in skeletal muscle pathology resulting from acute injury and Duchenne muscular dystrophy (DMD) in mice. Methods: Expression changes and muscular localization of mouse cathelicidin‐related antimicrobial peptide (Cramp) were examined in the skeletal muscle of normal mice treated with chemicals (cardiotoxin and BaCl2 ) or in dystrophic muscle of DMD mouse models (mdx, mdx/Utrn +/− and mdx/Utrn −/− ). Cramp penetration into myofibres and effects on muscle damage were studied by treating synthetic peptides to mouse skeletal muscles or C2C12 myotubes. Cramp knockout (KO) mice and mdx/Utrn/Cramp KO lines were used to determine whether Cramp mediates muscle degeneration. Muscle pathophysiology was assessed by histological methods, serum analysis, grip strength and lifespan. Molecular factors targeted by Cramp were identified by the pull‐down assay and proteomic analysis. Results: In response to acute muscle injury, Cramp was activated in muscle‐infiltrating neutrophils and internalized into myofibres. Cramp treatments of mouse skeletal muscles or C2C12 myotubes resulted in muscle degeneration and myotube damage, respectively. Genetic ablation of Cramp reduced neutrophil infiltration and ameliorated muscle pathology, such as fibre size ( P  < 0.001; n  = 6) and fibrofatty infiltration ( P  < 0.05). Genetic reduction of Cramp in mdx/Utrn +/− mice not only attenuated muscle damage (35%, P  < 0.05; n  = 9–10), myonecrosis (53%, P  < 0.05), inflammation (37–65%, P  < 0.01) and fibrosis (14%, P  < 0.05) but also restored muscle fibre size (14%, P  < 0.05) and muscle force (18%, P  < 0.05). Reducing Cramp levels led to a 63% (male, P  < 0.05; n  = 10–14) and a 124% (female, P  < 0.001; n  = 20) increase in the lifespan of mdx/Utrn −/− mice. Proteomic and mechanistic studies revealed that Cramp cross‐talks with Ca 2+ signalling in skeletal muscle through sarcoplasmic/endoplasmic reticulum Ca 2+ ‐ATPase1 (SERCA1). Cramp binds and inactivates SERCA1, leading to the activation of Ca 2+ ‐dependent calpain proteases that exacerbate DMD progression. Conclusions: These findings identify Cramp as an immune cell‐derived regulator of skeletal muscle degeneration and provide a potential therapeutic target for DMD.